the horizontal line must have the same y coordinate so y=14
3∅ can be rewritten as (2∅+∅)
sin(3∅) = sin(2∅ + ∅<span>)
Opening brackets on the right hand side;
= sin2</span>∅ cos ∅ + cos2∅sin<span>∅
</span><span>This simplifies to;
= 2sin</span>∅cos^2∅ + sin∅ (1- 2sin^2∅<span>)
= sin</span>∅ (2cos^2∅ + 1 - 2sin^2∅<span>)
= sin</span>∅ (2(1 - sin^2∅) +1-2sin^2∅<span>)
= 3sin</span>∅ - 4sin^3<span>∅</span>
Well i got 130.
hope it helps : )
I am so sorry this is the wrong answer
Answer:
Step-by-step explanation: 14
Simplify ——
x :
14
(2x - ——) - 7
x